Use of tie-in femur osteosynthesis in free-living aracuã scamoso (ortalis squamata) with blockage of the femoral and ischiatic nerves (International Seven Journal of Multidisciplinary, 2024)
We report the case of an adult scaly-breasted arachnid, which arrived for treatment with a history of being on the ground in the courtyard of a house, unable to stay in a station. On clinical examination, the bird had an immobile right femur, with a probable comminuted fracture, and the decision was made to perform a surgical procedure to correct the fracture. The treatment used the tie-in technique, where a 1.2 mm intramedullary pin was placed in the femur for initial alignment of the bone fragments, while external fixation was carried out with three pins of the same thickness as the previous one, two in the cranial region and one in the region distal to the fracture site. Two months after the surgery, an X-ray was taken to check for the formation of bone callus, with a satisfactory result. The external fixator was removed the following day, and seven days after removal the bird was discharged and released. As well as the tie-in technique having a high success rate with a complete return of function, it has the advantage that its implants are removable, which is important when the animal is returned to the wild, preventing these implants from remaining in the environment if it dies.